Parametric Optimization in EDM of Ti-6Al-4V using Copper Tungsten Electrode and Positive Polarity: a statistical approach - Rahman, Md. Mustafizur; Khan, Md. Ashikur Rahman; Kadirgama, Kumaran; Maleque, Md. Abdul; Abu Bakar, Rosli (WSEAS Press, 2011)
This paper explores the develop optimized model to investigate the effects of peak current,pulse on time and pulse off time in electric discharge machining (EDM) performance on titanium alloy utilizing copper tungsten as electrode and positive polarity of the electrode. The experiments are carried out on Ti6Al4V. Experiments were conducted by varying the peak current, pulse on time and pulse off time and the corresponding values of surface roughness (SR) were measured. A mathematical model for correlating influences of these variables and surface finish of the workpiece is developed in this paper. Design of experiments (DOE) method and response surface methodology (RSM) techniques are implemented. The validity test of the fit and adequacy of the proposed models has been carried out through analysis of variance (ANOVA). The obtained results evidence that as the surface roughness increases with peak current and pulse on time increases. The effect of pulse off time on surface roughness changes with peak ampere. The excellent surface finish is investigated in this study at short pulse on time. The optimum machining conditions in favor of surface roughness are estimated and verified with proposed optimized results. It is observed that the developed model is within the limits of the agreeable error when experimental. This result leads to desirable surface roughness and economical industrial machining by optimizing the input parameters.